Moderating Role of Emotional Intelligence in Organizational Cynicism and Organizational Citizenship Behaviour in a Sample of Lecturers - C.E Ikpenwa; E.A Okonkwo; M.A Ezeh; N.V Okonkwo; I.N Azike (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
This study investigated the moderating role of emotional intelligence in organizational cynicism and organizational citizenship behaviour in a sample of lecturers. Three hundred and nineteen participants comprising 207 males and 112 females between the ages of 30 - 70 (M=51.61, SD =10.26) were drawn through multi-stage (cluster and criterion). The study was a cross-sectional survey in which Emotional Intelligence Scale (Davies et al, 2010), Organizational Cynicism Scale (Dean, et al, 1998) and Organizational Citizenship Behaviour Scale (Smith, Organ & Near 1983) were administered for data collection. Moderated hierarchical multiple regression analysis was used for data analysis. The results indicated that emotional intelligence and organizational cynicism jointly predicted organizational citizenship behaviour among university lecturers (ΔR2 = .067, P<. 01). Cognitive, affective and behavioural components of organizational cynicism jointly predicted organizational citizenship behaviour (ß=.22, P<. 05). Behavioural component of organizational cynicism independently predicted organizational citizenship behaviour (ß=.22, P<. 05). The dimensions of emotional intelligence (appraisal of own emotion, appraisal of others emotion, regulation of own emotion, regulation of others emotion and utilization of emotion jointly moderated the prediction of organizational citizenship behaviour by organizational cynicism (R2 = 0.155, ΔR2 = 0.30, P<. 001). Only utilization of emotion dimension of emotional intelligence independently and negatively moderated the prediction of organizational citizenship behaviour by organizational cynicism (ß = -.32, P<. 05). It has been recommended that policy makers in the University should create conditions that will boost the emotional intelligence especially utilization of emotions of lecturers in order to cushion off the negative effects of organizational cynicism on organizational citizenship behaviour of their workforce.